Analisis Usaha Pengolahan Amplang Ikan Bandeng (Chanos chanos) Di Kelurahan Muara Sembilang Kecamatan Samboja Kabupaten kutai Kartanegara - Eko Wahyudi; Helminuddin; Wahyu Fahrizal (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
Eko Wahyudi, 2022. Analysis of Milkfish Amplang Processing Business in Muara Sembilang Village, Samboja District, Kutai Kartanegara Regency (Supervised by Prof. Dr. Ir. H. Helminuddin.,MM and Wahyu Fahrizal, S.Pi.,M.P). The purpose of this study is to determine the profit of milkfish amplang processing business (Chanos chanos) based on business analysis which includes: Revenue Cost Ratio (RCR), Price Break Event Point, Sales Point Break Event, Production Point Break Event, Payback Period, Return On Investment and knowing the factors that become obstacles and drivers of milkfish amplang processing business. This research was conducted from March 2022 to June 2022. The type of research data used is qualitative data with primary data sources obtained from interviews using questionnaires that are guided by a list of questions made according to the research objectives. The results showed that the value of RCR = 2.33, the breakeven point of the price was Rp. 10,000/pack < actual price of Rp. 4.285/pack, the break-even point of sales is Rp. 9.057.326/month < actual sales of Rp. 45,000,000 per month, the break-even point of production is 889 packs/month < the actual production is 4500 packs/month, the payback period is 3 months, and the results of the ROI analysis are 224%. The results of the overall business analysis show that the milkfish amplang (Chanos chanos) processing business in Muara Sembilang Village, Samboja District, Kutai Kartanegara Regency is profitable and feasible to run. Keywords: Amplang Processing, Milkfish, Business Feasibility.